Study of compliance to prescribed lighting standards in hospitals of Delhi NCR, India - Garg, Neeraj; Kant, Sunil; Gupta, Shakti Kr; Garg, Ruchi (International Journal of Research in Medical Sciences, 2017)
Background: An adequate level of lighting is essential for clinical, diagnostic and other processes in hospitals. This study has been conceptualised to assess the existing lighting standards in Indian hospitals. Carefully designed lighting can transform the appearance of a space, making it attractive, welcoming and either restful or stimulating depending on the effect created. It can enhance the architectural appearance of the space and contribute to orientation and way finding. Methods: Select hospitals of Delhi NCR were visited and the existing level of luminance in various areas of the hospital were recorded and analysed against prescribed National and International standards. The existing lighting standards in different areas of the hospital were assessed against the prescribed Indian standards given under National Lighting Code 2010 of India (2) and IS 4347: Code of practice for hospital lighting in India. Results: There has been a gap in the existing and prescribed lighting standards in all the hospitals considered in this study. This study revealed that none of the Hospital was having 100% compliance to the prescribed lighting standards. The best compliance was with hospital ‘A’ (56.5%), which is a private Corporate Hospital and worst with hospital ‘E’ (8.7%), a govt. hospital. The areas where compliance was highest was OT complex (100%) and circulation areas (60% ) while service areas have least compliance rate (20%), with only hospital ‘A’ having 50% compliance and others having 0% compliance. As far as wards are concerned, 80% of the Hospitals adhere to the prescribed lighting standards for general lighting and lighting at nursing station, but none of the hospitals adhere to the prescribed lighting standards for patient examination, reading lights for patients and night lighting. At the entrance 100% hospitals adhere to the prescribed lighting standards. The major reason cited by the concerned hospital authorities was the unawareness on the prescribed lighting levels and standards. Conclusions: Major conclusions drawn from this study are there are identified gaps in the existing lighting standards in the Hospitals and the recommended lighting levels and standards. Compliance to lighting standards in Indian Hospitals range from 8.7% to 56.7%, with majority of the hospitals in the range of 26% to 35%.There is as urgent need to sensitise the environment regarding recommended lighting standards.